COMPUTATIONAL THINKING-BASED FIQH LEARNING STRATEGIES IN PESANTREN - Khusnuniyah, Hindhun; Achmad, Syaefudin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
The purpose of this research is to find out the learning strategy of fiqh based on Computational Thinking in Islamic boarding schools. This research uses descriptive qualitative methods, which are included in the type of field research. The data sources used are primary and secondary data. Data collection was carried out through interviews, observations, and documentation. The data was then checked for validity through triangulation. After the data is collected, it is analyzed by data reduction, presentation, and conclusion drawing. The results showed that the Computational Thinking-based fiqh learning strategy in understanding santri fiqh material was taught by implementing indicators such as decomposition, pattern recognition, abstraction, and algorithm as a tool for understanding santri fiqh and direct practice for santri. Computational Thinking-based fiqh learning strategies can increase students' understanding of the material to be more in-depth. This research can be a new treasure and reference in organizing learning in Computational Thinking-based pesantren.